OBSERVATIONS OM THE PLANKTON OF THE COCHIN BACKWATERS - George, M J (Indian Journal of Fisheries, 2016)
Considerable work, both qualitative and quantitative, has been done on the plankton of Indian coastal waters in recent years. But the plankton of Indian backwaters has received little attention so far. Sewell (1913, 1924 and 1934) has studied plankton, more especially the copepods, of the Chilka Lake and the salt lakes of Calcutta. The brackish water fauna of Adyar backwaters was studied by Panikkar and Aiyar (1937). Chacko etal. (1953, 1954 o, 1954 A and 1954 c) have made brief references to planktonic organisms also in their studies on the hydrobiology and fisheries of various lakes and estuaries of Madras. A preUminary study of the plankton of the Chilka Lake has been made recently by Devasundaram and Roy (1954).